Persiapan Food and Beverage Banquet BNDCC sebagai Venue G-20 FM and CBG Working Dinner - Chiarakania Chaniago; Sudarno Sudarno (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2021)
Banqueting is a large meal or feast. On the other hand, banquet have a service on a feast that already planned before complete with main courses and deserts, room and needed equipment. In venues such as Bali Nusa Dua Convention Center (BNDCC) banquet work is necessary. Banquet have many tasks to do until it become three division, FB banquet, FB service and FB kitchen. Writer will bring G-20 Finance Ministers and Central Bank Governor’s (G-20 FM & CBG) Working Dinner one of VIP meeting of Annual Meetings 2018 International Monetary Fund – World Bank Group (IMF-WBG) that handled by banquet operation, which is FB banquet and FB service. The meeting are held on October 11th, 2018 ini Singaraja 2, lantai 2, BNDCC 1, Nusa Dua, Bali. By this time, writer use observation and documentation analysis. This research will be given to the company and Politeknik Negeri Jakarta as graduation requirement in 7th semester, MICE study program, trade administration department.